St. Gregory of Nyssa: The Life of St. Macrina - Panczova, Helena (Forum Theologicum Sardicense, 2025)
Helena Panczova, St. Gregory of Nyssa: The Life of St. Macrina. This paper examines the content, form, and dating of Macrina’s death. In the second part, the imagery of the ‘philosophic’ life is analysed in greater detail, including the evolving meaning of this term, the role of education in Christian life, and the significance of a woman assuming the role of teacher.